2013
DOI: 10.1161/circulationaha.112.000974
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Aortic Root Size in Elite Athletes

Abstract: and atrium (Appendix I in the online-only Data Supplement). In addition, we manually reviewed the references of included studies Background-The aorta is exposed to hemodynamic stress during exercise, but whether or not the aorta is larger in athletes is not clear. We performed a systematic literature review and meta-analysis to examine whethere athletes demonstrate increased aortic root dimensions compared with nonathlete controls. Methods and Results-We searched MEDLINE and Scopus from inception through Augus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
104
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(106 citation statements)
references
References 45 publications
2
104
0
Order By: Relevance
“…Therefore, marked aortic root dilatation should be considered a pathological process in athletes. 35 …”
Section: Aortamentioning
confidence: 99%
“…Therefore, marked aortic root dilatation should be considered a pathological process in athletes. 35 …”
Section: Aortamentioning
confidence: 99%
“…However, very few studies have explored this issue. 1 A challenge surrounding aortic root dilation in athletes is the definition of the upper limits of this anatomic segment. Recent guidelines of the European Society of Cardiology state that aortic diameters do not usually exceed 40 mm.…”
mentioning
confidence: 99%
“…3,4 Another issue is that most studies have only categorized sports as either strength-type or endurance-type. 1 Nevertheless, Mitchell et al provide a more detailed classification determined by the static and dynamic components of each sport. 5 The aim of this study is to establish the physiological limits of aortic remodeling associated with prolonged and intense exercise training in a large population of healthy elite athletes, taking into account cardiovascular demands of each sport in terms of static and dynamic component as stated in Mitchell's sport classification.…”
mentioning
confidence: 99%
“…D'Andrea et al [4] concluded that the aortic root dimension was significantly greater in strength-trained athletes (n=245) than in age-and gender-matched endurance athletes (n=370). On the contrary, Iskander et al [5] showed that male endurance athletes had greater AO diameters incomparison to strength athletes and controls, and strength athletes showed a non-significant trend towards greater dimensions at AO than controls. Pelliccia et al [6] assessed athletes of 28 different sports disciplines (n=1300) and showed that the aortic root dimension could be explained by weight, height, left ventricular mass and age, with the type of sports having a significant but lower impact.…”
Section: Aortic Root Dimensioonmentioning
confidence: 94%